The Role of Social Media in Shaping the attitudes of Damascus University Students towards the Covid-19 Vaccine (Damascus University Journal of arts and humanities sciences, 2023)
The researcher in this study aimed to identify the role of social Media in shaping the attitudes of Damascus University students towards the Covid-19 vaccine, this study belongs to descriptive research based on the survey method by distributing a questionnaire to a quota sample of 100 individuals from Damascus University students. The study concluded with the following results: It has been proven that there is a correlation between the degree of respondents dependence on social Media to obtain information about the Covid -19 vaccine and their attitude towards it. It was also found that the largest proportion of the respondents relied on Social Media to a moderate degree to obtain information about the vaccine, and the most important goals of their dependence on it is the desire to obtain advice and guidance to identify the benefits and advantages of the vaccine and its harms, the study also found that the majority of respondents trust Social Media to obtain information about the vaccine to a moderate degree, and that the largest proportion of the respondents was neutral attitudes towards the Covid-19 vaccine
Keywords: : Social Media; Attitudes of Damascus University Students; Covid-19 Vaccine